Influence of Near Fault Earthquakes with Forward Directivity and Fling Step on Seismic Response of Steel Box-Girder Bridge - Baig, Mirza Aamir; Ansari, Md. Imteyaz; Nazrul Islam; Umair, Mohammad (International Journal of Sustainable Construction Engineering and Technology, 2023)
The existing bridge seismic design guidelines that rely on the ground acceleration in the far fault zone, ignore the potential impact of near fault forward directivity and fling-step effects on the bridge structures. In the current study probabilistic seismic damage evaluation of a continuous four-span box girder bridge under the impact of near-fault forward directivity and fling step effect is studied employing the fragility analysis. The incremental dynamic analysis is used to construct the fragility curves which shows a range of damage states from minor to collapse for the different damage metrics and for the considered peak ground acceleration varying between 0.1g and 1.2g. Damage metrics such displacement pier ductility, rotational pier ductility and displacement of girder are used to develop the fragility curves and the probabilistic seismic damage model. To evaluate the bridge vulnerability, a probabilistic seismic damage assessment is performed using an ensemble of forward directivity and an ensemble of fling-step comprising permanent ground offset. The suggested probability-based earthquake damage framework is anticipated to be a well-versed model able to estimate the seismic damages to the continuous box girder bridges while taking into account the variation of near fault earthquakes. The findings show that, even at low PGA values the forward directivity and the fling-step ground motions represent a significant risk to the bridge.